Self‐reported levels of occupational stress and wellness in forensic practitioners: Implications for the education and training of the forensic workforce. Issue 4 (1st March 2021) - Goldstein, Justin Z.; Alesbury, Helen S.
Abstract: While there is extensive research into wellness and mental health risks for police officers and other first responders, a smaller portion of research has considered how forensic practitioners are affected. This study surveyed 211 forensic practitioners from the American Academy of Forensic Sciences membership, the Clark County Office of the Coroner/Medical Examiner, and the New York City Office of Chief Medical Examiner to assess current wellness perceptions within forensics. The 22‐question survey focused on (a) how the demands of daily casework affect self‐perceived burnout levels, (b) whether mental health issues are adequately addressed during the education and training of the forensic workforce, and (c) whether forensic professionals are getting the wellness support that they themselves feel that they need. Basic descriptive statistics, chi‐square (χ 2 ) cross tabulations, and correlation analyses were constructed to assess relevant relationships within survey responses. Results indicate that forensic professionals report a high level of burnout and a lack of sufficient wellness resources in their current professional climate. While professionals feel fulfilled from their work, the majority of respondents (73.9%) felt that common mental health issues that exist in their profession were not adequately addressed during their workplace training, academic schooling, or professional certification. Despite the uniformly weak correlations observed between variables, chi‐square analyses reveal practically and statistically significant trends that warrant further investigation, particularly in the context of vicarious trauma. Overall, this study provides an important baseline for future wellness research to support the specialized needs of forensic scientists during their training and education.